The Effect of Sales Growth, Company Size, and Liquidity on Profit Growth in the Transportation and Logistics Sector Listed on the BEI in 2020-2023 - Puja Rizki Shintia Putri; Elvi Rahmi (Universitas Negeri Padang, 2024)
This study examines how sales growth, firm size, and liquidity affect profit growth in logistics and transportation companies listed on the BEI between 2020 and 2023. With a sample of 24 businesses chosen through purposive selection, the study focuses exclusively on companies in this industry. The analysis makes use of secondary data obtained from financial statements. The results, which were obtained by using A surge in sales growth, have a favorable and significant impact on profit growth. Liquidity has a little and inconsequential impact on profit growth, whereas the company’s size has no noticeable effect. However, sales growth, company size, and liquidity significantly affect profit growth. In light of these results, companies are encouraged to enhance profitability by implementing strategies that optimize operational efficiency, manage liquidity prudently, and drive sales growth. The size of a company has minimal effect on profit growth; therefore, focusing on innovation is more beneficial, and high-quality services and sustainable growth strategies are recommended.